The effects of personality traits on entrepreneurial intention and creativity among Chinese and African college students in era of industry 4.0/5.0 - Xu, Miaoxin (Frontiers in Psychiatry, 2023)
Using samples of Chinese and African college students, this paper explored the effect of personality traits on entrepreneurial intention and creativity from the boundaryless career perspective. The empirical results showed that both Chinese and African college students’ conscientiousness and openness had significantly positive effects on entrepreneurial intention and creativity respectively, and boundaryless mindset had a mediating effect in the relationship between conscientiousness, openness, entrepreneurial intention and creativity. However, the moderating effects of GPA were quite different. While Chinese college students’ GPA strengthened the positive effect of boundaryless mindset on entrepreneurial intention and creativity respectively, African college students’ GPA weakened the positive effect of boundaryless mindset on entrepreneurial intention and had no significant moderating effect on the relationship between boundaryless mindset and creativity. This study was based on the empirical research of Chinese and African college students through a combination of contrastive and advance study methodology. It has provided new perspectives for exploring influencing factors and effects of employment performance in the context of Industry 4.0/5.0 and it has made theoretical and practical contributions to promote creativity and entrepreneurial intention.